Pertanggungjawaban Hukum Rumah Sakit Terhadap Kelalaian Tenaga Medis Yang Mengakibatkan Pasien Cacat Permanen - Adiana, I Nyoman; Pidada, Ida Bagus Anggapurana; Herawati, Kadek Mery (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Article 46 Law no. 44 of 2009 stated that "Hospitals are legally responsible for all losses incurred due to negligence committed by health workers at the Hospital". Hospital responsibilities in providing health care are based on professional, ethical, civil, administrative and criminal aspects. The hospital law provides protection and guarantees for patients and medical personnel involved in health services. And also provide certainty in the hospital to maximize management functions, regulate and control various things that are the responsibility of the hospital so that it can minimize various things that can certainly harm patients. Obstacles are the difficulty in finding evidence related to medical negligence committed by medical personnel against patients which causes harm to patients so that it is difficult for hospitals to prove the existence of medical negligence committed by medical personnel against patients. The solution is for the hospital to form a team to deal with acts of negligence that occur, accredit professional and health workforce resources, evaluate the performance of medical personnel, and improve hospital management. Conduct accreditation of professional and health workforce resources.